Measuring continuance participation in online communities - Shanmugam, Mohana; Jusoh, Yusmadi Yah; Jabar, Marzanah A.; Nor, Rozi Nor Haizan (Little Lion Scientific, 2017)
Social commerce is an emerging digital trend that involves participation from online communities. Members of online communities have become influential in ensuring the prolonged usage of social commerce sites. Drawing on the theories of planned behavior and social support as well as satisfaction and perceived value constructs, the purpose of this manuscript is to propose a continuance participation measurement framework. The framework integrates pertinent constructs that drive continuance participation measurement process, which applies the weighted checklist method. A simulation is performed to measure the significance level of online community sites. Additionally, data gathered from four experts confirm the efficacy of the proposed framework. The simulation discussed serves as a guideline and can be useful for developers and managers of social commerce sites for measuring the performance of their online community sites.